Health Behaviors and Loneliness in Young Adults (Medical Forum Monthly, 2024)
Objective: To study the relationship of Health Behaviors with loneliness.Study Design: Cross- Sectional Study.Place and Duration of Study: This study was conducted in Lahore College for Women University, Lahore from January to June, 2015. Materials and Methods: Health Behavior Checklist1 and the Loneliness Scale2 were employed in the study. The sample comprised 240 students selected through systematic random sampling from Government College University and Lahore College for Women University.Results: Results showed that preventive health behaviors had a negative correlation with loneliness whereas risk taking behaviors were positively correlated with loneliness. Moreover the male participants had higher scores on the emotional loneliness subscale in comparison to the female participants who scored higher on the social loneliness subscale.Conclusion: As loneliness increases the engagement in preventing health behaviors decreases. Similarly the same increase in loneliness is linked with increased risk taking behaviors.